(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The promulgation of the Alternative Learning System (ALS) Act aims to strengthen quality education for all Filipino citizens in an inclusive way. In response to this, DepEd Region III implemented ALS 2.0 which is aligned with the K to 12 Curriculum and the inclusion of Senior High School as an ALS implementing unit. This explanatory sequential mixed-method study assessed the implementation of the ALS 2.0 strategic plan vis-à-vis its weaknesses and threats that turned into opportunities for the enhancement of ALS 2.0 in public Senior High Schools. The findings of the study revealed that the ALS 2.0 strategic plan was described as implemented. More so, it appeared that the respondents had the same view on the implementation of ALS 2.0 in their schools. The observed weaknesses and threats fell on teaching and learning and linkages. These were utilized as opportunities and points of improvement for ALS SHS in Region III. The proposed ALS strategic plan enhancement aimed to address the gap of the ALS 2.0 implementation. This study affirmed the concept of goodness-of-fit between the ALS 2.0 strategic plan and Deming’s theory of Total Quality Management in improving the plan implementation of the school implementing unit.